Ventral prefrontal cortex structure and function in behavioural change - Neubert, F (2015)
There is a considerable interest in the neural correlates of cognitive flexibility, language, valuation, credit assignment and decision-making. The ventrolateral, orbital and medial prefrontal cortex together with their long-range connections with the rest of the brain are thought to be critically involved in these cognitive processes. My thesis explores human and monkey ventrolateral, orbital and medial prefrontal cortex and their potential role in flexible adaptation and choice. In the introductory chapter I review neuroeconomic and neuro-ecological views of decision making, as well as modular versus connectionist views of brain structure and function. In the second and third chapter I investigate the connectivity of ventrolateral, orbital and medial prefrontal cortex and compare their sub-regions between humans and monkeys. Overall I report a striking degree of similarity of connectivity profiles across species even though these regions are thought to support uniquely human cognitive abilities such as language, social cognition, prospective planning and strategic decision-making. This may be taken to suggest that higher order cognitive functions “re-use” a neural apparatus that is shared with macaque monkeys. In the fourth chapter I present a parcellation of the white matter into the major long-range association fibre systems based on their projection patterns to the cortical surface. These findings may have implications not only for the cross-species comparison of connectivity-profiles but also for understanding some psychiatric and neurological disorders as "disconnection syndromes". I conclude by evaluating whether a modular view of brain structure and function is consistent with a view that portraits the brain as changeable, highly adaptive and strongly interconnected.